Análise exploratória espacial da criminalidade no estado do Rio Grande do Sul - Grings, Maicon (2015)
The purpose of this study is to analyze the impact of socioeconomic variables in the indexes of economic crimes in the state of Rio Grande do Sul. Thus, a descriptive analysis of economic crimes and crimes against the individual took place. Then, it was necessary to map crime, to identify each cluster group of crimes under study; and finally identify factors that may influence the rates of economic crimes for the State of Rio Grande do Sul. The theme shows importance, since it depicts one of the biggest problems faced by contemporary society. Therefore, discussions about the topic promote inferences that provide the creation of public policies aimed to combating crime. In order to meet such a proposal, this study was based on models of the Space Econometrics. For the implementation of the study, secondary databases were used from official sources such as the Department of Public Security of Rio Grande do Sul State (SSP / RS), Institute of Applied Economic Research (IPEA), Brazilian Institute of Geography and Statistics (IBGE) and the Department of SUS (DATASUS). As a result, it highlights the space concentration of economic crimes, especially in the metropolitan area of Porto Alegre and the coastal region of the state. It also highlights the positive effect that IFDM variables - income and employment, Bolsa Familia and GINI Index presented in relation to the dependent variable Economic Crimes, and the negative effect that the variable rate of illiteracy presented regarding the dependent variable. Among the conclusions of this research, there is the motivational issue involving each group of crime. It plays an important role in the commission of the tort, that is verified by the spatial distribution of crime in the state. The Bolsa Familia program, contrary to what was expected, did not appear as a variable that tends to help decrease crime rates against property in the state of Rio Grande do Sul. It is concluded, finally, that the concentration of income is the main variable that causes the increase in economic crimes. However, education is the main factor that helps reduce economic crimes in the state of Rio Grande do Sul.